IDENTIFICATION OF FRONT PATTERNS IN THE WATERS AROUND RUMAHTIGA AND GALALA-HATIVE - Erick Sipahelut; Simon Tubalawony; Yunita Angnetjie Noya (Universitas Mataram, 2024)
The waters of Ambon Rumahtiga and Galala-Hative Kecil are part of the waters of Ambon Bay which connects Outer Ambon Bay (TAL) and Inner Ambon Bay (TAD). The characteristics of the waters are influenced by the tides and the input of fresh water which flows into the surrounding waters. This research aims to analyze front events both horizontally and vertically based on the distribution of temperature, salinity and water density. The research was conducted in August 2023 at 9 observation stations. Temperature, salinity and density measurements were carried out in-situ using a CTD (CTD type), and analysis of the vertical and horizontal distribution of temperature, salinity and density using ODV software version 5.6.2 and Surfer 12. Front analysis used a quantitative discrete method approach by comparing differences in temperature, salinity and density characteristics. The research results show that a front is formed on the water surface to a depth of 5 m between the water mass moving from TAD (Station 8) with a temperature of 26.16-26.58 oC, salinity of 30.98-33.37 Psu and sigma-t of 19.92 -21.64 Kg/m3 and water mass from TAL (Station 5) with a characteristic temperature of 25.97 oC, salinity of 33.03-34.22 Psu and sigma-t of 21.47-22.47 Kg/m3. Front events also occur between water masses with temperature characteristics of 26.17-26.32 oC, salinity 34.12-34.32 Psu, sigma-t 21.66-22.30 Kg/m3 (Station 6) with water masses with temperature characteristics 26.43-26.41oC, salinity 33.37-34.22 Psu and sigma-t 21.66-22.42 Kg/m3 (Station 9). Tidal currents and freshwater input that flows from the Wairuhu River are the causes of fronts.